2015
DOI: 10.1016/j.cherd.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration of glucose: Analysis of parameters and membrane characterization

Abstract: Please cite this article as: Almazán, J.E., Romero-Dondiz, E.M., Rajal, V.B., Castro-Vidaurre, E.F.,Nanofiltration of glucose: analysis of parameters and membrane characterization, Chemical Engineering Research and Design (2014), http://dx.doi.org/10. 1016/j.cherd.2014.09.005 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
4
13
0
3
Order By: Relevance
“…With the value of r p in hand, the value of DX/A k could be calculated from the Hagen-Poiseuille equation (eqn (18)), in which the pure water permeability J w /DP was approximately 2.269 Â 10 À11 m Pa À1 s À1 at pH 3, as determined by a pure water permeate experiment. Indeed, this value of J w /DP was similar to that reported by Almazán et al 26 (i.e., 2.79 Â 10 À11 m Pa À1 s À1 ). Thus, the r p and DX/A k values calculated from the model were 0.395 nm and 1.661 mm, respectively, and so these values were employed in the following DSPM-DE model.…”
Section: Calculation Of the Model Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…With the value of r p in hand, the value of DX/A k could be calculated from the Hagen-Poiseuille equation (eqn (18)), in which the pure water permeability J w /DP was approximately 2.269 Â 10 À11 m Pa À1 s À1 at pH 3, as determined by a pure water permeate experiment. Indeed, this value of J w /DP was similar to that reported by Almazán et al 26 (i.e., 2.79 Â 10 À11 m Pa À1 s À1 ). Thus, the r p and DX/A k values calculated from the model were 0.395 nm and 1.661 mm, respectively, and so these values were employed in the following DSPM-DE model.…”
Section: Calculation Of the Model Parameterssupporting
confidence: 91%
“…The water consumption efficiency in the diananoltration process is described as eqn (26). The inhibitors remove efficiency is described as eqn (27) The recovery rate of monosaccharides is described as eqn (28)…”
Section: Mass Balance Equations In Diananoltrationmentioning
confidence: 99%
“…Paul et al [ 33 ] propose that the viscosity of the solvent penetrating through the membrane may be the underlying cause for the non-linear transport. Almazán et al [ 34 ] suggest that concentration polarization and rise of osmotic pressure are the causes for the decline of flux through the membrane due to increased resistance to permeation. Further, it was suggested that glucose as an uncharged organic molecule, but with a high dipole moment (~14 Debye) is more likely to be repelled by a membrane charge [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Al iniciar los experimentos con una membrana de alta de presión se necesita un acondicionamiento previo de la misma. Para ello, se realizó un lavado de la membrana con el que se eliminó el gel protector que la recubre, tal y como indica el fabricante, haciendo circular por el sistema agua desionizada durante dos horas a una presión de 8 bares (Zhao et al, 2010, Almazán, Romero-Dondiz, Rajal, & Castro-Vidaurre, 2014. El agua de alimentación utilizada para la realización de los ensayos corresponde a aguas sintéticas preparadas en el laboratorio a 10 mg/L de cada metal.…”
Section: Metodología Utilizada En Los Experimentos De Filtración Con Membranasunclassified